Early diagenesis, sedimentary dynamics and metal enrichment reveal deep-sea ventilation in Magellan Seamounts during the middle Pleistocene - Shen, Zhongshan; Chen, Yanping; Mikhailik, Pavel; Cai, Yun; Wang, Haifeng; Yi, Liang (Frontiers in Marine Science, 2024)
Seamounts are ubiquitous topographic units in the global oceans, and the Caiwei Guyot in the Magellan Seamounts of the western Pacific is a prime example. In this study, we analyzed a well-dated sediment core using magnetic properties, sediment grain-size, and metal enrichment to uncover regional ventilation history during the middle Pleistocene and explore potential linkages to global climate changes. Our principal findings are as follows: (1) The median grain size is 3.3 ± 0.2 μm, and clay and silt particles exhibit minimal variation, with average values of 52.8 ± 1.8 % and 38.2 ± 1.6 %, respectively, indicating a low-dynamic process; (2) Three grain-size components are identified, characterized by modal patterns of 3 μm (major one), 40 μm, and 400–500 μm, respectively; (3) Magnetic coercivity of the deep-sea sediments can be classified into three subgroups, and their coercivity values are 6.1 ± 0.5 mT, 25.7 ± 1.0 mT, and 65.2 ± 2.1 mT. Based on these results, we propose a close linkage between magnetic coercivity and metal enrichment, correlating with changes in deep-sea circulation intensity. Conversely, sediment grain-size changes seem to be more strongly influenced by eolian inputs. Consequently, we suggest that reginal ventilation has weakened since 430 ka, likely linked to a reduction in Antarctic bottom water formation.